Students' AI Usage Behavior in Final Project Writing: A Library Service Interaction Perspective - Dwi Putra, Dedy (Knowledge Garden: International Journal of Library Studies, 2025)
Introduction: The growing trend of artificial intelligence (AI) utilization in academic settings has significantly influenced students' approaches to writing their final projects. This study explores how students adopt AI tools during the thesis writing process and investigates the mediating role of information-seeking behavior and library service interaction. The study aims to identify the extent to which students’ perceptions of usefulness and ease of use of AI influence their behavior in accessing information and engaging with academic support services, particularly at the Universitas Brawijaya Library. Method: This research employed a quantitative method with a structural equation modeling–partial least squares (SEM-PLS) approach. Data were collected from 200 final-year undergraduate and graduate students through a structured questionnaire. The study utilized the Technology Acceptance Model (TAM) and Information Seeking Behavior (ISB) theory as its analytical framework. Results: The findings show that perceived usefulness and perceived ease of use significantly influence both students’ information-seeking behavior and their interaction with library services. These two mediating variables, in turn, have a significant impact on the intensity of AI use in academic writing. Indirect effect analysis further confirmed that the strongest pathway to AI adoption is through active information seeking, rather than through direct perceptions alone. Discussion: The discussion highlights the critical role of librarians as facilitators in bridging students' access to AI-related knowledge and tools. Their guidance supports the ethical and effective use of AI in higher education. Recognizing these roles allows libraries to transform into centers of digital academic literacy. Conclusions: Fostering information-seeking habits and enhancing librarian-student interaction are key to promoting responsible AI integration. Future research should consider longitudinal studies and multi-campus comparisons to further generalize these findings.